The Lompe code: A Python toolbox for ionospheric data analysis - Hovland, A. Ø.; Laundal, K. M.; Reistad, J. P.; Hatch, S. M.; Walker, S. J.; Madelaire, M.; Ohma, A. (Frontiers in Astronomy and Space Sciences, 2022)
A recent paper by Laundal et al. (2022c) presented a new technique to combine all available measurements of polar ionospheric electrodynamics; magnetic field measurements from ground and space, ionospheric convection data from radars and satellites, and conductance measurements; to a full 2D map within analysis regions of arbitrary resolution and extent. The technique, called Local Mapping of Polar Ionospheric Electrodynamics (Lompe), is implemented in Python Laundal et al. (2022a). The Lompe technique combines spherical elementary current system analysis, finite element analysis on a cubed-sphere projection, the use of empirical models like the International Geomagnetic Reference Field, and visualization tools. In this paper, we go through these different components of the Lompe code and show how they are useful on their own, for example in the analysis of ground magnetometer data or data from the upcoming Electrojet Zeeman Imaging Explorer mission. We also demonstrate how to use the Lompe code to produce a coherent picture of ionospheric electrodynamics.